2021
DOI: 10.1177/08901171211055312
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Dreams, and Nightmares During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has affected the sleep and dreams of many individuals. Some have experienced improvements, while others have had more complaints. The changes to daily life such as working from home and spending more time indoors in confinement may have disturbed the circadian rhythms of some individuals. There were many reports of a shift towards a later bedtime during the pandemic, with several studies showing that in general, females experienced worse sleep than males, including more nighttime awakenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Circadian misalignment, developed during the pandemic, could explain the aforementioned sleep disturbances. Lockdown and atypical work/school schedules resulted in reduced sunlight exposure and daily physical activity [ 52 ••, 77 ]. Additionally, increased screen time (i.e., increased use of smartphones and social media) has been shown to impair the secretion of melatonin [ 77 ].…”
Section: Sleep Disorders In General Population During Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Circadian misalignment, developed during the pandemic, could explain the aforementioned sleep disturbances. Lockdown and atypical work/school schedules resulted in reduced sunlight exposure and daily physical activity [ 52 ••, 77 ]. Additionally, increased screen time (i.e., increased use of smartphones and social media) has been shown to impair the secretion of melatonin [ 77 ].…”
Section: Sleep Disorders In General Population During Covid-19 Pandemicmentioning
confidence: 99%
“…Lockdown and atypical work/school schedules resulted in reduced sunlight exposure and daily physical activity [ 52 ••, 77 ]. Additionally, increased screen time (i.e., increased use of smartphones and social media) has been shown to impair the secretion of melatonin [ 77 ]. The flexibility of work/school schedule could allow individuals to sleep more in synchrony with their circadian tendency, promoting greater circadian alignment.…”
Section: Sleep Disorders In General Population During Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Drs. Kennedy 6 and Grander outline how the pandemic resulted in changes to sleep patterns and quality including atypical work schedules, increased screen time, and pandemic-related stress. Their review found evidence that the pandemic has resulted in later bed times and more sleeping hours.…”
mentioning
confidence: 99%
“…4,5 Drs. Kennedy 6 and Grander outline how the pandemic resulted in changes to sleep patterns and quality including atypical work schedules, increased screen time, and pandemic-related stress. Their review found evidence that the pandemic has resulted in later bed times and more sleeping hours.…”
mentioning
confidence: 99%